Urban Morphological Parameters of the Main Cities in China and Their Application in the WRF Model - Yong Sun; Ning Zhang; Shiguang Miao; Fanhua Kong; Yizhou Zhang; Nana Li (Journal of Advances in Modeling Earth Systems, 2021)
Abstract As one of the effective ways to study urban climate and environmental problems, the performance of numerical model could be improved in urban areas by enhancing the description of urban morphology. One of the largest challenges faced by researchers is the lack of real urban canopy parameters (UCPs) to represent urban morphological characteristics. In this study, the urban morphological parameters were estimated and a high‐resolution urban morphological parameter data set for the main cities in China was developed. The results show that the distribution of urban morphological parameters is of regional characteristics and cities in China are mainly dominated by low‐rise buildings. Chinese cities can be broadly divided into two types based on the probability distribution of building height: single‐peak and double‐peak. The number of low‐rise buildings in single‐peak cities is much larger than that of double‐peak cities, which contributes to the difference between the two types of cities. The equivalent street width of northern cities in China is higher than that of southern cities, and the equivalent building width is almost the same. However, the default UCPs of the Weather Research and Forecasting (WRF) model distort the morphology of Chinese cities. The sensitivity of the WRF model to urban morphological parameters was also investigated in Nanjing. Overall, our results indicate that urban morphological parameters have a significant influence on the energy balance process in cities and improve the performance of the WRF model in simulating the air temperature and canopy wind speed.